The relationship between take-off parameters and relative vertical momentum of free limbs at the take-off in hurdle clearance - Ozaki, Y.; Ueda, T. (Journal of Human Kinetics, 2024)
This study aimed to clarify the kinetics of the relative vertical momentum to the proximal joint of each free limb and their contribution to the increase in the centre of mass height at the take-off of hurdle clearance, as well as their relationship with take-off variables. Thirteen male hurdlers cleared one hurdle at the height of their centre of mass, and their attempts were filmed using six high-speed cameras. The hurdle height was 96.54 ± 2.63 cm (55.35 ± 0.29% of body height). The approach distance was set at 15 m and adjusted by each hurdler in the range of 10-50 cm so as not to involve any noticeable step length adjustment before the take-off. The combined free limb relative vertical momentum tended to increase until mid-support and was maintained until the toe off. The smaller the whole-body vertical momentum at the toe off and the increase in relative vertical momentum of the lead leg during the take-off, the higher the take-off velocity, the shorter the support time, and the smaller the deceleration. The higher the relative vertical momentum of the forward swing arm during touchdown and the smaller the relative vertical momentum increase of the combined free limb and the forward swing arm during the take-off, the smaller the deceleration. In conclusion, hurdlers should reduce the increase in whole-body vertical momentum at the take-off by suppressing the increase in relative vertical momentum of the lead leg and the forward swing arm.